Chad basin and rural development authproty maiduguri statistical book 1973-1983 - chad basin and rural development authority (Maiduguri-Nigeria chad basin rural development authority, 1983)
This statistically book examines the activities of the chad basin development authority between 1973-1983 with emphasize to rural development projects in Maiduguri State Nigeria.
asm; 16/04/19
Loans
Keywords: Economic development projects; Maiduguri-Nigeria